10u-3=9u-6

Simple and best practice solution for 10u-3=9u-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10u-3=9u-6 equation:


Simplifying
10u + -3 = 9u + -6

Reorder the terms:
-3 + 10u = 9u + -6

Reorder the terms:
-3 + 10u = -6 + 9u

Solving
-3 + 10u = -6 + 9u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-9u' to each side of the equation.
-3 + 10u + -9u = -6 + 9u + -9u

Combine like terms: 10u + -9u = 1u
-3 + 1u = -6 + 9u + -9u

Combine like terms: 9u + -9u = 0
-3 + 1u = -6 + 0
-3 + 1u = -6

Add '3' to each side of the equation.
-3 + 3 + 1u = -6 + 3

Combine like terms: -3 + 3 = 0
0 + 1u = -6 + 3
1u = -6 + 3

Combine like terms: -6 + 3 = -3
1u = -3

Divide each side by '1'.
u = -3

Simplifying
u = -3

See similar equations:

| 7f-8=6f | | 5x+y+4x-y=360 | | -0.146x^2+0.96x+7.5=0 | | 4x-y=55 | | s=2cos(0) | | -26+7p=2(7p-6) | | -8(8k-8)-3=-6k+3 | | (3x-1)(2x-5)=(3x-1)(x+2) | | 4n+27= | | 5n+18= | | 6=3*-9+21 | | 6(-2-6n)-4n=268 | | 2=4x-3+5x-8-6x-3 | | 147=-1-4(3+5m) | | (21x+2)= | | -2-6n=-4(1+2n) | | x+y=5y=3 | | 3+4t=4y+3 | | 9a-2a=8b-4b | | 25=3.75(6)+2.5 | | 36x^2=96x | | n-3/4=1(1/2) | | 2x-7=3x+0.25 | | l=50-1w | | 8(x-2)-5=4-3(x+1) | | -36+6v=4(6v+4)+2 | | -18.08-12.1g-11.48=-4.3g+18.8 | | 5x+20=36-x | | (x/2)=(6/5) | | 3w-16=-1+2-14w | | 2cos2x/2sin2x | | 24x^2-4x-54=6 |

Equations solver categories